Energy coupled to matter in additive manufacturing for controlled magnetic heterogeneity through multi-material consolidation - Malaya Prasad Behera; Yifan Lv; Sarat Singamneni (Materials & Design)
Magnetism assisting the manufacturing process is well known within the energy coupled to matter realm and material processing assisting in the magnetic responses has also been in practice. The current research is an attempt to combine both approaches together in a multi-magnetic material consolidation process under the influence of external magnetic fields. Additive manufacturing by selective laser melting with controlled dispersion of multi-material magnetic powders and the application of controlled magnetic fields during material melting and consolidation are key features of the methodology. The melt-pool geometries, sub-granular structures, and the crystallographic orientations showed distinct responses with the use of external magnetic fields during laser consolidation of NdFeB and FeCo systems and their combinations with and without a third non-magnetic material matrix. As per the energy coupled to matter mechanisms and mechanics, the multi-magnetic material substrates consolidated by laser melting under external fields demonstrated patterned polar formations and predefined magnetic orientations. The directions and intensities of the north and south poles at different regions of the printed samples depend on the strengths and orientations of the external fields applied during consolidation and magnetisation fields employed after printing.